KONSERVASI TANAMAN LADA (Piper nigrum L.) SECARA IN VITRO - YELNITITIS YELNITITIS; NURLIANI BERMAWIE (Jurnal Penelitian Tanaman Industri, 2001)
In vitro conservation of black pepper (Piper nigrum L.)Black pepper (Piper nigrum L.) is one of the economically im¬ potant spices. The major constraint in black pepper cultivation and conservation in ield is foot rot disease caused by Phytopthora capsici which could cause plants die. Conservation of black pepper germplasms as living collections in ield is risky due to pests and natural disaster. The experiment on in vitro cop ervation of black pepper var. LDL was conducted al the laboratory of Plant Genetic Resources and Breeding, Research Institute for Spice and Medicinal Crops (RISMC) Bogor from April 1998 to Maret 1999. Single node cuttings from sterile culture were used as explains. The explains were cultured on Murashige and Skoog (MS) medium on full and half strength concentration supplemented with paclobutrazol (paclo) (0, 1, 3 and 5 mg/1). The experiment was performed in a randomized complete block design arranged factorially with 10 replications. The result showed that the medium supplemented with paclo on both full MS and MS A medium could suppress vegetative growth until 12 months. There was no signiicant interaction between medium and paclo on shoot initiation. The effect was signiicant on shoot height, number of leaves and culture performances. Increasing paclo concen¬ tration caused higher suppression of plant growth. MS A medium supplemented with paclo 5 mg/1 showed the slowest growth with shool height 2.10 cm and number of leaves 9. Culture performance was fresh, with green leaves and vigorous. Advcntive shoots were able to regenerate on the medium supplemented with BA 0.3 mg/1. In vitro conservation of black pepper with paclo did not change plant regeneration ability. Therefore, this technique may be used as an altenative method for black pepper conservation.